Pengaruh Metode Pembelajaran Problem Solving Terhadap Kemampuan Membaca Kritis Siswa Kelas VIII SMPN 4 Marioriawa (INDONESIAN LANGUAGE TEACHING & LITERATURE JOURNAL, 2023)
This study aims to describe the effect of problem solving learning method on critical reading ability of grade VIII students of SMPN 4 Marioriawa. This research is a quantitative research with one group pretest-posttest design. This research involved VIII grade students of SMPN 4 Marioriawa totalling 35 people. The data collection technique in this study used a multiple choice test totalling 20 questions. The results of data analysis showed that: (1) the critical reading ability of grade VIII students of SMPN 4 Marioriawa before the application of problem solving learning method was categorised as low with an average score of 10.37; (2) the critical reading ability of grade VIII students of SMPN 4 Marioriawa after the application of problem solving learning method was categorised as high with an average score of 16.26; and (3) the results of hypothesis testing showed that the sig. (2-tailed) value of 0.000 <0.05, so it is concluded that there is an effect of problem solving learning method on critical reading ability of grade VIII students of SMPN 4 Marioriawa.